2022
DOI: 10.1021/acscatal.1c05012
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Catalytic Performance through In Situ Encapsulation of Ultrafine Ru Clusters within a High-Aluminum Zeolite

Abstract: Zeolite-encapsulated metal clusters have been shown to be an effective bifunctional catalyst for tandem catalysis. Nevertheless, the efficient encapsulation of nanometric metal species into a high-aluminum ZSM-5 zeolite still poses a significant challenge. In this contribution, we have prepared well-dispersed and ultra-small Ru clusters encapsulated within a high-aluminum ZSM-5 zeolite (with a Si/Al ratio of ∼30–40) via an in situ two-stage hydrothermal synthesis method. Small Ru clusters with an average size … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(31 citation statements)
references
References 56 publications
1
27
0
Order By: Relevance
“…with FAU, RuO2@FAU exhibited an obvious decrease in the micropore volume from 0.217 to 0.177 cm 3 •g −1 and surface area from 506 to 424 m 2 •g −1 (Table 1). It indicated that ruthenium particles were successfully encapsulated into FAU cages [19]. The hydrogen temperature-programmed reduction result of RuO2@FAU was given in Figure 1C.…”
Section: Synthesis and Characterization For Ruo 2 @Fau Catalystsmentioning
confidence: 89%
See 1 more Smart Citation
“…with FAU, RuO2@FAU exhibited an obvious decrease in the micropore volume from 0.217 to 0.177 cm 3 •g −1 and surface area from 506 to 424 m 2 •g −1 (Table 1). It indicated that ruthenium particles were successfully encapsulated into FAU cages [19]. The hydrogen temperature-programmed reduction result of RuO2@FAU was given in Figure 1C.…”
Section: Synthesis and Characterization For Ruo 2 @Fau Catalystsmentioning
confidence: 89%
“…RuO 2 clusters have been successfully encapsulated in LTA (8 MR) for methanol oxidation [16], in MFI (10 MR) for phenol hydrodeoxygenation [17] and in FAU (12 MR) for aerobic alcohol oxidation [18]. Yang et al [19] found that metal-acid intimacy played an essential role in enhancing the production of cyclohexane. Particularly, few works have been reported on the application of encapsulated RuO 2 clusters in the decarboxylation of L-lysine.…”
Section: Introductionmentioning
confidence: 99%
“…kinds of CO adsorption at 2090, 1994-2011, and 1890 cm −1 , which is attributed to multi-coordinated Ru n+ −CO, linear Ru 0 −CO, and bridging Ru 0 −CO species, respectively. [34][35][36] The main adsorption is linear Ru 0 −CO, and it showed a blue shift on Ru/H-Z5 (1997-2011 cm −1 ) compared with that on Ru/SiO 2 and Ru/Al 2 O 3 (1994 cm −1 ). The relatively high transition energy of adsorbed CO species on Ru/H-Z5 resulted from the strong interaction between Ru and H-Z5, which caused an electron-deficient Ru metal as the electron of Ru was extracted by H-Z5 with more Brønsted acid sites, and consequently induced a larger blue shift of CO adsorption on the catalyst.…”
Section: Surface Acidic and Electronic Propertiesmentioning
confidence: 99%
“…The greater number of OSDAs could interact strongly with metal precursors, hindering the successful construction of the zeolite structure. It is gratifying that a two-step hydrothermal synthesis method of low-temperature nucleation and high-temperature crystallization was used, and metal precursors were added after nucleation to successfully achieve the encapsulation of ultrasmall Ru clusters in high aluminum ZSM-5 (Si/Al = 30–40) 85 (Fig. 9a).…”
Section: Direct Hydrothermal Synthesis For Metal@zeolite Catalystsmentioning
confidence: 99%
“…85 27 Al MAS NMR spectra of (b) H-ZSM-5, (c) Ru/ H-ZSM-5-IP and (d) Ru@H-ZSM-5. 85 (e) Content distribution of different Al species for different samples. 85 able catalyst sources.…”
Section: Multistep Synthesis For Metal@zeolite Catalystsmentioning
confidence: 99%